Dynamics of skill acquisition - Button, C.; Davids, K.; Chow, J. Y.; Seifert, L.; Araújo, D. (Human Kinetics, 2020)
Humans operate in information-rich, dynamic environments and require complex coordination patterns to interact with surfaces, objects, and events. An important challenge for movement scientists is to understand how coordination patterns are assembled, controlled, and acquired. In the early 21st century there has been an increasing interest in the societal constraints that shape and influence the acquisition of movement skills. Do the resources of the digital age affect how we learn skills? Will our changing environment invite us to move in different ways? The study of human movement now bridges many related disciplines, including motor development, motor control, psychology, biology, and physical therapy. Although we attempt to apply our discussion of movement as broadly as possible throughout this book, we will often use movement models from Sports and exercise as examples to describe key ideas. As Sports and recreation enthusiasts ourselves, we recognize that such movement models can provide particularly rieh task constraints in which to study and understand important aspects of movement behavior (Davids, Button, Araüjo, Renshaw, and Hristovski, 2006). One of the main objectives of physical educators, Sport scientists, movement scientists, psychologists, and physiotherapists is to develop valid conceptual models of human movement behavior that are based on research (Post, Pijpers, Bosch, and Boschker, 1998). The development of a comprehensive model of motor control is necessary before one can consider issues related to learning, but this in itself is not a simple task, because "the story of even a simple movement will have intentional, mechanical, informational, neural and muscular chapters" (Michaels, 1998, p. 65). It is now clear that a rigorous model of human movement requires a multidisciplinary framework to capture the interlocking scales of analysis (e.g., neural, behavioral, psychological) and the many Subsystems (e.g., perceptual and movement) involved in producing behavior. From a practical perspective, understanding how coordination and control are achieved promotes an informed Organization of learning and rehabilitation environments and more effective use of practice and therapy time (Vaz, Silva, Mancini, Carello, and Kinsella-Shaw, 2017). Studying these processes in human movement Systems is vital for considering issues involved in - becoming familiar with children`s movement capabilities at various stages of development; - interpreting movement disabilities and disorders and their effects on perceptual-motor function; - designing ergonomic equipment; - designing coaching, teaching, and training tasks; - planning and managing exercise prescription, therapeutic, and rehabilitation programs; - understanding the nature of individual differences at various levels of performance; - preventing injury and taking health and safety precautions; - understanding how to transmit information to learners and patients in rehabilitation; and - enhancing and maintaining quality of life for elderly people as their movement capabilities change. A conceptual model of coordination and control is important for designing learning environments, but it is also important for ensuring that learners have positive experiences when acquiring motor skills. Given the concern about the lack of physical activity and the poor movement competency shovvn in affluent societies (e.g., the United Kingdoms Our Healthy Nation report, the World Health Organization`s World Health Report, and New Zealand`s Healthy Eating-Healthy Action report), this type of knowledge is vital for the design of physical activity programs to provide the basic skills necessary for subelite sport and exercise paiticipation (Clark, 1995). The goal of this book is to outline a reliable and comprehensive model of human movement to provide a valid framework (i.e., concepts, methodological tools, and language) through which students and practitioners can understand and address these issues. In this second edition of Dynamics of skill Acquisition, has been added new chapters and updated the book with important new empirical research findings and theoretical insights that have emerged since the first edition was written.